2008
DOI: 10.1051/0004-6361:20078796
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter observations of planetary nebulae

Abstract: Aims. We present 43 GHz (7 mm) observations of a sample of radio-bright Planetary nebulae aimed to obtain, together with far-IR measurements (IRAS), reliable estimates of the fluxes emitted in the millimetre and sub-millimetre band, and, therefore, to test their detectability by the forthcoming ESA PLANCK mission. This spectral range, even though very important to constrain the physics of circumstellar environments, is still far from being completely exploited. Methods. The new millimetre 43 GHz observations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Yet in our data the effect is not observed. This conclusion is in agreement with new observations of planetary nebulae at 43 GHz (Umana et al 2008), whose measurements are mostly in agreement within errors with those presented in this paper (with exception for PN IC2165 (221.3-12.3)).…”
Section: Analysis Of Flux Density Resultssupporting
confidence: 93%
“…Yet in our data the effect is not observed. This conclusion is in agreement with new observations of planetary nebulae at 43 GHz (Umana et al 2008), whose measurements are mostly in agreement within errors with those presented in this paper (with exception for PN IC2165 (221.3-12.3)).…”
Section: Analysis Of Flux Density Resultssupporting
confidence: 93%
“…Sieber et al (1981) are shown by squares. The other flux densities shown were reported at 330 MHz (Rengelink et al 1997), 1420 MHz (Condon et al 1998;Pineault et al 1993), 4.85 GHz (Becker et al 1991), 30 GHz (Pazderska et al 2009), and 43 GHz (Umana et al 2008) and shown by open circles. The new λ6 cm and λ11 cm measurements are marked as filled circles.…”
Section: Discussionmentioning
confidence: 69%
“…In a previous paper (Umana et al 2008a), we published the flux density measurements of planetary nebulae (PNe).…”
Section: Introductionmentioning
confidence: 99%